Self-evaluating performance: an analysis of police integrity, professionalism and service provision from the South Pacific - Watson, Danielle (Policing and society, 2022)
Studies on policing in the Global South rarely discuss police self-evaluation of performance. Furthermore, internal performance assessments usually reflect the perspectives of senior management with little to no input from frontline officers. This paper seeks to present a more inclusive view of police performance as it presents the findings of a stakeholder perceptions survey commissioned by the Tuvalu Police Service (TPS) to examine police perceptions about their performance as service providers. We examine the survey responses of 100% of TPS officers on active duty (N=84) and 14 in-depth interviews to determine their views on the integrity, professionalism and service provision of TPS members. Findings indicate that police are able to provide useful assessments of the organisation and of their colleagues, but are less valid sources of information about personal performance. These findings are particularly relevant to discussions about improving police service provision in the developing world. The paper makes a contribution to policing scholarship by highlighting the potential of self-evaluation as an impetus for improved policing practices.